المقارنة بين إعطاء السميتيكون و N-أستيل سيستئين قبل التنظير الهضمي العلوي في تحسين الأداء التنظيري - إبراهيم علي; زعبلاوي يوسف; سلوم عالية (Latakia University Journal -Medical Sciences Series, 2017)
أجريت هذه الدراسة من أجل تقييم فعالية التحضير الدوائي بالسميتيكون أو N-أستيل سيستئين في تحسين الأداء التنظيري في المرضى الخاضعين للتنظير الهضمي العلوي .انها دراسة تجريبية Randomized Double –blind Clinical Trial شملت الدراسة 350 طفلا خضعوا لاجراء تنظير هضمي علوي بين عمر 6 أشهر و 15 سنة , تم تقسيم المرضى عشوائيا الى 3 مجموعات (المجموعة الاولى أعطيت Placebo و الثانية N-أستيل سيستئين و الثالثة سميتيكون) مع 10 مل ماء وقبل 20 دقيقة من التنظير الهضمي العلوي , تم تقييم كمية الفقاعات الهوائية و الرغوة المشاهدة أثناء التنظير وتقسيمها الى اربع درجات من0-3 درجة. قورنت درجة الفقاعات الهوائية والرغوة وكذلك مدة التنظير بين المجموعات الثلاث . كمية الفقاعات الهوائية و الرغوة كانت أقل بشكل كبير في مجموعة السميتيكون مقارنة مع placebo و N- أستيل سيستئين (P 0,0001) , كذلك مدة التنظير كانت أقل في مجموعة السميتيكون (P 0,0001) This study was done to evaluate the effectiveness of premedication with simethicone or N- acetylcysteine (NAC) on enhancing endoscopic visibility in patient undergoing Esophagogastroduodenoscopy. This was a Randomized Double –blind Clinical Trial. The study included 350 children, ranged in age from 6 months to 15 years. patients were randomly allocated into three groups to receive one of the following premedications (: group 1 : Placebo, group 2: N- acetylcysteine, group 3: simehticone) with 10 ml of water at 20 minutes before Esophagogastroduodenoscopy .It was rated the amount of foam and air bubbles ,and divided into four degrees from 0 to3 degree, The scores of foam and air bubbles were compared and the duration of endoscope also compared between the three groups. The amount of foam/air bubbles was significantly lower in the simeticone group compared with the placebo and NAC group (p 0,0001) The duration of endoscopy was shorter in the simeticone group (P 0,0001)